Murji'ah and Legitimacy of the Umayyads - Shaban Ali Bidaki; Muhammad Sepehri; Mahmood Seyyed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Murji'ah was one of the political-intellectual groups that in the first century of Islam, by avoiding judging the beliefs and positions of the active factions in the field of politics and society, entered the arena of existence in the turbulent Muslim society. It seems that the dual function of the Murji'ah in history - compromise and confrontation with the government - and consequently the two-sided judgment about them, the duality in their thought and, better, the ambiguous nature of the word Murji'ah and its specific definition of faith, that is, the two main pillars of reference thinking go back. For this reason, the term Murji'ah has been used for a range of different intellectual and political currents and sometimes contradictions, and even in the case of Kharijites and Shiites. The central issue of the present study is what the type of confrontation and reaction of the Murji'ah difference in compromising and confronting the Umayyads was? The aim of this study is to show how the Umayyads used this dual Murji'ah approach to legitimize themselves. This research has been organized with a critical approach to previous research and with a descriptive-analytical view.